Quantitative Scrutinization of Aflatoxins in Different Spices from Pakistan. (3rd October 2016) - Naz, Narjis; Kashif, Aiza; Kanwal, Kinza; Khan, Abdul Muqeet; Abbas, Mateen
Abstract : The current research work aimed to access the contamination level of aflatoxins B1, B2, G1, and G2 in the household spices that are widely consumed in huge amounts. 200 different spice samples, 100 packed and 100 unpacked, were analyzed for the aflatoxins profile by HPLC with an incidence of 61.5% contamination out of which 53.66% samples exceed the EU limit. The results disclosed that the unpacked samples are more contaminated as compared to the packed samples except for white cumin seeds. Among packed and unpacked samples of spices, the maximum value of aflatoxins was detected in fennel, that is, 27.93 μ g/kg and 67.04 μ g/kg, respectively. The lowest concentration of aflatoxin was detected in cinnamon in packed form (0.79 μ g/kg) and in the unpacked samples of white cumin seeds which is 1.75 μ g/kg. Caraway seeds and coriander in its unpacked form showed positive results whereas black pepper (packed and unpacked) was found free from aflatoxins. This is the first report on the occurrence of aflatoxins in packed and unpacked samples of spices from Pakistan. To ensure safe consumption of spices, there should be constant monitoring of aflatoxin and more studies need to be executed with the intention of preventing mycotoxin accretion in this commodity.